The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1309/te56-a43x-29tt-5h8g
|View full text |Cite
|
Sign up to set email alerts
|

CD5– Mantle Cell Lymphoma

Abstract: Mantle cell lymphoma (MCL) typically expresses B-cell antigens and CD5 and overexpresses bcl-1 protein. However, unusual cases of bcl-1+ and CD5-MCL have been observed, posing a practical challenge for correct diagnosis and management. We identified 25 cases (48 samples) of bcl-1+ and CD5- lymphoma. CD5 expression was assessed by flow cytometric analysis alone (1 case), immunohistochemical analysis alone (17 cases), or dual flow cytometric/immunohistochemical methods (7 cases). The morphologic features were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 32 publications
4
63
2
2
Order By: Relevance
“…Absence of CD5 expression has been described in up to 10% of all MCL cases. 22 However, reports of cases that have converted from a CD5-positive to a CD5-negative immunophenotype, or that show concurrent CD5-positive and CD5-negative tumors at different sites are unusual. 23 Reports of aberrant CD10 expression by MCL are also rare, and most often associated with blastoid morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of CD5 expression has been described in up to 10% of all MCL cases. 22 However, reports of cases that have converted from a CD5-positive to a CD5-negative immunophenotype, or that show concurrent CD5-positive and CD5-negative tumors at different sites are unusual. 23 Reports of aberrant CD10 expression by MCL are also rare, and most often associated with blastoid morphology.…”
Section: Discussionmentioning
confidence: 99%
“…While distinguishing the CD5-negative cases from marginal zone lymphoma becomes more difficult, CD5-negative MCL cases are occasionally reported. 3,14,15 Liu et al 3 reported 25 cyclin D1-positive, CD5-negative MCL cases, where centrocyte-like cells proliferated in 20 cases and blast-like cells proliferated in 5 cases. Similarly to other reports, CD5-negative cases were observed in about 10% of MCL cases, warning of the risk of diagnosis sorely depending on CD5 phenotypes, and suggesting that immunohistochemical examinations such as cyclin D1 are required regardless of CD5 phenotypes when MCL is suspected clinically and morphologically.…”
Section: -13mentioning
confidence: 99%
“…In addition, a few CD5-negative cases have been reported. 3 The prognosis is poor, with an overall survival rate of about 3 years, and it is not generally curable by chemotherapy. Histologically evaluable prognostic factors include mitotic figure increase (> 20 mitotic figures per 10 high-power fields) 4 and Ki-67-positive cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of CD5 expression has been reported in a minority of cases, perhaps 5-10% of MCL overall. 65 A newer marker useful in the differential diagnosis of MCL is SOX11, which is positive in 490 of cases and may be particularly helpful if Cyclin D1 staining is suboptimal or otherwise difficult to interpret. 47,66 SOX11 expression has also been reported in cases recently identified as Cyclin D1-negative MCL (see Variant-Cyclin D1 Negative MCL section).…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%